Tunable electromagnetically induced transparency in coupled three-dimensional split-ring-resonator metamaterials - Han, Song (2018)
Metamaterials have recently enabled coupling induced transparency due to interference effects in coupled subwavelength resonators. In this work, we present a three dimensional (3-D) metamaterial design with six-fold rotational symmetry that shows electromagnetically induced transparency with a strong polarization dependence to the incident electromagnetic wave due to the ultra-sharp resonance line width as a result of interaction between the constituent meta-atoms. However, when the six-fold rotationally symmetric unit cell design was re-arranged into a fourfold rotational symmetry, we observed the excitation of a polarization insensitive dual-band transparency. Thus, the 3-D split-ring resonators allow new schemes to observe single and multi-band classical analogues of electromagnetically induced transparencies that has huge potential applications in slowing down light, sensing modalities, and filtering functionalities either in the passive mode or the active mode where such effects could be tuned by integrating materials with dynamic properties.